2015
DOI: 10.1007/s11738-015-1824-9
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic characteristics of the subtending leaf and the relationships with lint yield and fiber quality in the late-planted cotton

Abstract: To investigate the photosynthetic characteristics in the subtending leaf of cotton (Gossypium hirsutum L.) boll (LSCB), and their relationships with lint yield and fiber quality under cool temperature due to late planting, field experiments during 2009 to 2011 were conducted using two different cool temperature-tolerant cultivars, Kemian 1 (temperature-tolerate) and Sumian 15 (temperature-sensitive), at three planting date (25 April, 25 May and 10 June) in Nanjing (118°50 0 E, 4 32°02 0 N), China. First, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…1 and 2), consistent with previous studies (Pettigrew, 1995;Zhao and Oosterhuis, 2000;Shu et al, 2008). In addition, there were significant interactions of cultivar × planting date and/or cultivar × shading treatment on fiber length and strength, and the significant interaction of planting date × shading treatment on fiber length and Micronaire, which were partly consistent with previous studies Liu et al, 2015). However, there was non-significant difference in the interaction of cultivar × planting date × shading treatment for the three traits of fiber quality.…”
Section: Cotton Fiber Quality Formationsupporting
confidence: 91%
See 2 more Smart Citations
“…1 and 2), consistent with previous studies (Pettigrew, 1995;Zhao and Oosterhuis, 2000;Shu et al, 2008). In addition, there were significant interactions of cultivar × planting date and/or cultivar × shading treatment on fiber length and strength, and the significant interaction of planting date × shading treatment on fiber length and Micronaire, which were partly consistent with previous studies Liu et al, 2015). However, there was non-significant difference in the interaction of cultivar × planting date × shading treatment for the three traits of fiber quality.…”
Section: Cotton Fiber Quality Formationsupporting
confidence: 91%
“…cotton and under shading. Through analyzing the CVs of lint yield and yield components, it was shown that boll weight was significantly affected by LP, and boll number was significantly affected by shading, consistent with other studies (Cao et al, 2011;Lv et al, 2013;Liu et al, 2015). However, most of previous studies were focus on the effects of LP or shading in cotton yield.…”
Section: Tablesupporting
confidence: 83%
See 1 more Smart Citation
“…Fiber quality is strongly affected by growth environments (e.g., plant density, irrigation, fertilization, weather events) and there is limited understanding of the relationship between cultivars, fiber quality, and planting date [3,18]. Late planted cotton produces superior quality fiber (e.g., increased elongation and low micronaire), but low fiber length and strength [19][20][21].In cotton production systems, soil phosphorus (P) unavailability is considered a major limiting factor to lint yield formation due to the sustained capacity of leaf photosynthetic characteristics [22]. Despite high P application rates, low solubility, low mobility, and high fixation by the soil matrix limits its availability to the plants [23].…”
mentioning
confidence: 99%
“…Fiber quality is strongly affected by growth environments (e.g., plant density, irrigation, fertilization, weather events) and there is limited understanding of the relationship between cultivars, fiber quality, and planting date [3,18]. Late planted cotton produces superior quality fiber (e.g., increased elongation and low micronaire), but low fiber length and strength [19][20][21].…”
mentioning
confidence: 99%